Instalación y evaluación de sistemas de riego por goteo para el cultivo de hortalizas en casa sombra para la región Chorotega y Brunca bajo el marco del proyecto Mesoamerica sin hambre de la representación de FAO en Costa Rica - Rodríguez-Bejarano, Emmanuel (Instituto Tecnológico de Costa Rica, 2018)
The characterization of the actual shade house’s irrigation systems was possible through in-field samples acquisition and analysis. Also, these results, gave the parameters for designing new irrigation systems, giving the opportunity to implement the feedback received from the analysis of the installed systems, allowing to generate systems better adapted to the real conditions in field. Finally, it is found that the irrigation systems are very susceptible to develop problems due to pressure lack or drip clogging with a mean irrigation uniformity of 80%. Also, there were designed two irrigation systems, transferring the knowledge necessary to assure the equipment’s appropriate installation and operation.
Proyecto de Graduación (Licenciatura en Ingeniería Agrícola) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Agrícola, 2018
Keywords: RLAF; Riego por goteo; Sombra; Evaluación; Uniformidad; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Area technology::Agricultural engineering